Perception and knowledge of dental interns toward interdepartmental coordination for successful prosthodontic treatment: A pilot study - Kamal Shigli; Pradnya Kakodkar; Neha Agrawal; Mamata Hebbal; Dayanand Huddar; M Vikneshan (Wolters Kluwer Medknow Publications, 2015)
Background: The graduating dentist should be trained in providing treatment utilizing the interdisciplinary approach because of the rapid advancements and increase in patient expectations, which demands for collaboration between the different specialists. Purpose: A pilot study was undertaken with an aim to assess the perception and knowledge of dental interns toward interdepartmental coordination for successful prosthodontic treatment. Subjects and Methods: Dental interns from two dental colleges in Sangli (India) participated in the study. A 24-item self-administered, structured closed-ended questionnaire was used to collect the data. Four questions assessed the perception and 20 questions assessed the knowledge, which were based on the four domains viz.: General, Endodontics, Orthodontics, and Prosthodontics. They were framed from case scenarios reporting to the Department of Prosthodontics, which required interdepartmental consultation. The questionnaire was validated before its application and reliability were also assessed. The final score for each question was calculated based on the correct responses. Descriptive analysis was calculated using the frequencies, percentages, and mean values by using SPSS 16 software. Results: Among 117 interns who participated in the study, 79.5% reported that they lacked training in an interdisciplinary approach. Approximately, 96% reported that the curriculum should be designed to include interdisciplinary training. Nearly, 88% reported that specialist from different specialty should be posted in one interdisciplinary department. Around 60% reported that they did not have the confidence of treating the patient as a whole. When the overall mean scores were considered, the highest scores were obtained for the general domain (95.3) and the lowest for the prosthodontic domain (83.6). Conclusion: The dental interns perceived that they lacked training in interdisciplinary approach, and the curriculum should include interdisciplinary training.